REKLAMASI PANTAI DAN PENGARUHNYA TERHADAP LINGKUNGAN FISIK DI WILAYAH KEPESISIRAN KOTA TERNATE - Herry Djainal (Universitas Islam Sultan Agung, 1970)
The purpose of this research is to study the reclamation process and investigate the impact of coastal reclamation to the spatial growth and also the change of spaceÂ function in coastal area of Town Ternate. The research method being used is descriptive qualitative. Technique or way of data collecting was done through the survey of institutional secondary data, that supported or equiped by the primary data which conducted through interview and field checking. Sampel taking and determination of checkingpoint in field was done by purposive sampling. Analysis model of the coastal reclamation process was presented in the form of tables of frequency and percentage, while verification of the affect of coastal reclamation was conducted phenomenal descriptively.The result of the research indicate that the coastal reclamation process in Sub-District Gamalama has taken place before the releasing of governmental policy of Town Ternate to do the coastal area settlement of Town Ternate in the year 2001. From 56 respondent which doing reclamation; 97,6 % are the firm, while the society member are 2,4 % from total vast of the reclamation land. The one that owning the permission of coastal reclamation of 99,96 % and the 0,04 % do not have the permission of reclamation withÂ total land of 192 m2. Whereas 67,86 % using talud, while which do not use the talud was counted of 32,14 % with vast land of 1625 m2 or equal to 0,31 %.The affect of coastal reclamation and the change of space function cover of :Â a) the change of flow pattern had not been identified yet, but from the existing data, the sea outflow around the research area always chopp round to follow the ebb situation. b) floods that happened in three location are more dominant influenced by the bad urban drainage system, coastal reclamatin do not influence directly to the floods. c) coastal reclamation given the negative impact to depth of the sea and sedimentation, have been occured the change of the depth of sea water at the waterworks around reclamation land, with the depth of water only reaching 1,5 metre, though its deepness ought to exceed 3 metre. d) occured the wide addition of land of 97.312,25 m2, but the land being used are more dominant for the using of bussiness place. e) had been occured the change of land/spastial function either in existing location or at the plan location that previously represent the coastal area that become the center of the town-economy service.Key Words : Reclamation, Environmental, Coastal Area